Antiviral drugs and vaccines currently used for COVID-19 - Łukasz Dobrek (Polish Pharmaceutical Society, 2023)
The beginning of the 21st century was marked by the emergence of the SARS-CoV-2 virus, which is the infectious cause of COVID-19 disease. The disorder is characterized by various courses and symptoms mostly arising from the upper and lower respiratory tract. Within a short period of time, the SARS-CoV-2 infection became a global pandemic and caused widespread global health, social and economic consequences. Due to the initial lack of possibility of causal treatment of the infection and specific methods of primary prevention, and in the face of the emergence of subsequent genetic variants of SARS-CoV-2, extensive and comprehensive research was undertaken to introduce new drugs with anti-coronavirus activity and novel vaccines enabling active immunization against COVID-19. The research resulted in the relatively quick registration of the first mRNA-based vaccines and vector vaccines as well as intruducing symptomatic treatment regimens for SARS-CoV-2 infection. The increasing knowledge regarding the COVID-19 pathophysiology allowed to identify new, potential target side of action of new compounds applicable in the treatment of COVID-19. They include agents with immunomodulatory effects (reducing the risk of a "cytokine storm" during infection), inhibitors of intracellular entry of SARS-CoV-2 (compounds against the superficial viral spike protein) or inhibitors of intracellular viral replication (nucleoside analogues, protease inhibitors). The aim of the study was to synthetically provide the up-to-date state of knowledge regarding currently used vaccines and specific antiviral treatment of COVID-19. The manuscript is a narrative review describing the pathophysiology of SARS-CoV-2 infection and COVID-19 symptomatology and briefly characterizing both the vaccines against COVID-19 currently registered by the European Medicines Agency (EMA) and/or the US Food and Drug Administration (FDA) (company products: BioNTech and Pfizer, Moderna Biotech Spain S.L., Janssen-Cilag International NV, Novavax CZ, a.s., AstraZeneca AB, Sanofi Pasteur, Valneva Austria GmbH and HIPRA Human Health S.L.U.). Moreover, antiviral drugs against SARS-CoV-2 infection (Tixagevimab / Cilgavimab, Anakinra, Nirmatrelvir / Ritonavir, Regdanvimab, Casirivimab / Imdevimab, Remdesivir, Sotrovimab, Tocilizumab, Baricitinib, Molnupiravir, Vilobelimab) were described.